THE PLACE OF PRONUNCIATION SPELLING IN TEACHER TRAINING - Demirezen, Mehmet (International Online Journal of Education and Teaching, 2020)
A pronunciation spelling (henceforth, PS) is supposed to represent a pronunciation more closely than a traditional spelling. The converse of spelling pronunciation is pronunciation spelling: the creation of a new spelling form on the basis of pronunciation. It indicates a pronunciation of a word that is influenced by its spelling and does not follow standard usage. In pronunciation spelling, there is the spelling of words intended to match a certain pronunciation more closely than the traditional spelling. They are frequently used in speech in colloquial English. It is also accepted as contraction, but this is not true because PS goes beyond contractions and has more complicated structures. In this research, the problem- causing influence of pronunciation spelling on 30 MA students in a foundation university was being investigated. It was discovered that after a three-hour intense teaching period the perception of the participants’pronunciation spelling on words, phrases, clauses, and sentences developed from 65 % to 76 %.